The effect of different low delivery rate drip irrigation systems on the physiological responses of citrus reticulata Blanco (Nadorcott) - Van Zyl, Gerrit Bruwer (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.